Local Sport Event Policies and Sustainability: A Puzzle Approach - Christian Tolstrup Jensen; Christian Tolstrup Jensen (Frontiers Media S.A., 2021)
As demands for more sustainable ways of living increase, organisers of sport events have come under increasing pressure to adapt. At the same time, more and more national and local event policies increase the demand for events. These two trends raise the question of how policy makers can combine the demand for events with a sustainable way of living; a question that so far has been subject to little research. The present paper analyses the conceptualisation of sustainability in all local policies relating to events in Norwegian municipalities. The paper is based on the analysis of policies covering 22 municipalities and includes both general development plans and more specific policies on events in its analysis. The analysis shows that all the municipalities have adopted a "broad" conceptualisation of sustainability, i.e., pursued a development, which should not limit the possibilities of future generations, in their general development plans. Although the general development plans serve as a basis for every other policy, the paper also shows that the municipalities in the specific policies for events often had "narrow" conceptualisation of sustainability, i.e., focusing on making local events reoccurring and/or increasing the capacity for hosting external events. The findings emphasise the relevance of looking at the local level when conducting future studies on events and sustainability and suggest that the practitioners acknowledge the complexity of reconciling demands for more events and increased sustainability.